Konsep Harga Adil Menurut Ibnu Taimiyah Relevansi dalam Ekonomi Modern - Maryam Fany; Sindi Setiawati; Shinta Puja Rinjani; Lina Marlina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study examines the concept of fair pricing according to Ibn Taymiyyah and its relevance in modern economics. In Ibn Taymiyyah’s perspective, fair pricing is not solely determined by market mechanisms but also by moral values and social balance. The aim of this study is to analyze Ibn Taymiyyah’s thoughts on fair pricing and its implications for today’s economic system. The research method used is a qualitative approach with literature analysis of Ibn Taymiyyah’s works and contemporary Islamic economic studies. The findings show that Ibn Taymiyyah’s concept of fair pricing reflects a balance supply and demand, based on principles of justice, transparency, and public welfare. This concept has the potential to serve as a solution to price disparities in the current global economy.